Adolescent idiopathic scoliosis: a review of current concepts. Issue 4 (April 2022) - Mohamed, Mohamed; Trivedi, Jayesh; Davidson, Neil; Munigangaiah, Sudarshan
Abstract: Adolescent idiopathic scoliosis is a common condition which is routinely seen in the outpatient department, with a prevalence of 5% in general population. It is important to be able to make this diagnosis but more importantly exclude other causes of scoliosis by carrying out a thorough history and examination. This paper will cover the pathophysiology, presentation, examination, and surgical management of adolescent idiopathic scoliosis.